Experimental Studies of Suction-Monitored Direct Shear Apparatus on Perth Poorly Graded Sand - Purwana, Y.; Jitsangiam, Peerapong; Nikraz, Hamid; Jotisankasa, A. (Australian Geomechanics Society, 2011)
Perth, Western Australia is a semi arid climate area. A soil characteristic at a near surface layer is relatively dry due to the deep water table, low humidity and high rate of evaporation. Subsurface exploration carried out in this study indicated that most soils in Perth are classified as poorly graded sand and remain dry along the year. Therefore, most Perth soils are considered to be in an unsaturated condition. The aim of this study is to evaluate the unsaturated Perth soil properties. Conventional and modified direct shear apparatuses were utilized in the shear strength evaluation of the saturated and unsaturated Perth soils. Modification of the direct shear apparatus was conducted by attaching a low capacity tensiometer to the direct shear top cap to measure the matric suction of the soil samples. The results indicate that during shear, suction is relatively low for a range of saturation degree of 50 to 100% and well within the tensiometer capacity, indicating that the modified direct shear apparatus is suitable for measuring the unsaturated poorly graded Perth sand.